Pengaruh Ukuran Kantor Akuntan Publik, Opini Audit, dan Audit Delay terhadap Auditor Switching: Studi Empiris Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Perdani, Levi Sukmi; Fauzihardani, Eka (Jurnal Eksplorasi Akuntansi, 2025)
The aim of this study was to examine the influence of public accounting firm size, audit opinion, and audit delay on auditor switching. The data utilized in this research were annual reports from mining companies listed on the Indonesia Stock Exchange between 2019 and 2023. The sample selection was conducted using the purposive sampling method. Logistic regression analysis was employed to analyze the data. The findings revealed that audit opinion has a significant relationship with auditor switching, while public accounting firm size and audit delay do not show a significant relationship with auditor switching. The next researcher can consider using other variables such as management changes, fee audit, financial distress and other variables that might influence auditor switching.